National Institutes of Health Stroke Scale (NIHSS) scoring inconsistencies between neurologists and emergency room nurses - Comer, Amber R.; Templeton, Evan; Glidden, Michelle; Bartlett, Stephanie; D'Cruz, Lynn; Nemati, Donya; Zabel, Samantha; Slaven, James E. (Frontiers in Neurology, 2023)
Background: Little is known about the consistency of initial NIHSS scores between neurologists and RNs in clinical practice. Methods: A cohort study of patients with a code stroke was conducted at an urban academic Primary Stroke Center in the Midwest between January 1, 2018, and December 31, 2019, to determine consistency in National Institutes of Health Stroke Scale Scores (NIHSS) between neurologists and registered nurses (RNs). Results: Among the 438 patients included in this study 65.3% (n=286) of neurologist-RN NIHSS scoring pairs had congruent scores. One-in-three, (34.7%, n=152) of neurologist-RN NIHSS scoring pairs had a clinically meaningful scoring difference of two points or greater. Higher NIHSS (p=<.01) and aphasia (p=<.01) were each associated with incongruent scoring between neurologist and emergency room RN pairs. Conclusions: One-in-three initial NIHSS assessed by both a neurologist and RN had a clinically meaningful score difference between providers. More severe stroke, as indicated by a higher NIHSS was associated with scoring inconsistency between neurologist-RN pairs. Subjective scoring measures, especially those involving a patient having aphasia, was associated with greater score incongruency. Score differences may be attributed to differences in NIHSS training requirements between neurologists and RNs.